Strategi Kepemimpinan Kepala Sekolah dalam Implementasi Program Sekolah Penggerak di SMKN 2 Mataram - Muhammad Muhari; M. Ary Irawan; Lu’luin Najwa (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study aims to analyze the leadership strategies of school principals in supporting the implementation of the Driving School Program at SMK Negeri 2 Mataram. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, non-participant observation, and document studies, then analyzed using an interactive model (data reduction, data display, conclusion drawing). Research subjects included the principal, vice principals, teachers, and educational staff. The findings reveal that the principal's leadership strategy is transformational-adaptive, manifested through: (1) intensive socialization and alignment of the school's vision and mission with the Merdeka Curriculum; (2) facilitation of infrastructure and establishment of learning communities; and (3) provision of motivation and discussion forums for teacher competency development. This strategy successfully created a school culture characterized by religiosity, achievement, independence, and strong character, despite challenges such as resource limitations and resistance to change. The study implies the critical role of leadership that is not only administrative but also inspirational and facilitative for the success of educational transformation at the vocational level. Key Words: Transformational Leadership, Driving School Program, Merdeka Curriculum, Vocational High School, Case Study Abstrak: Penelitian ini bertujuan menganalisis strategi kepemimpinan kepala sekolah dalam mendukung implementasi Sekolah Penggerak di SMK Negeri 2 Mataram. Pendekatan kualitatif dengan jenis studi kasus diterapkan. Data dikumpulkan melalui wawancara mendalam, observasi nonpartisipan, dan studi dokumentasi, serta dianalisis secara interaktif (reduksi, penyajian, penarikan kesimpulan). Subjek penelitian meliputi kepala sekolah, wakil kepala sekolah, guru, dan tenaga kependidikan. Hasil penelitian mengungkap bahwa strategi kepemimpinan kepala sekolah bersifat transformasional-adaptif, yang diwujudkan melalui: (1) sosialisasi intensif dan penyelarasan visi-misi dengan Kurikulum Merdeka; (2) fasilitasi sarana prasarana dan pembentukan komunitas belajar; serta (3) pemberian motivasi dan ruang diskusi untuk peningkatan kompetensi guru. Strategi ini berhasil menciptakan budaya sekolah yang religius, berprestasi, mandiri, dan berkarakter, meskipun dihadapkan pada tantangan keterbatasan sumber daya dan resistensi terhadap perubahan. Implikasi penelitian ini menekankan pentingnya kepemimpinan yang tidak hanya administratif, tetapi juga inspiratif dan fasilitatif untuk keberhasilan transformasi pendidikan pada jenjang vokasi. Kata Kunci: Kepemimpinan Transformasional, Sekolah Penggerak, Kurikulum Merdeka, SMK, Studi Kasus